Gender Bias in the Performativity of Arab Music: A Linguistic and Cultural Analysis of the Song “Talat Daqat” - Arini Najaya; Ahmad Hanim Syafril Alfalah; Anisatul Jannah; Laily Fitriani (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
This study aims to identify and analyze gender bias in the lyrics of the song Talats Daqat using Judith Butler’s theory of gender performativity as a critical linguistic approach. Butler’s theory posits that gender identity is not essential but is constructed through repeated social and cultural practices, including language and music. This qualitative research employs content analysis of the song lyrics as primary data, supported by a literature review on gender bias and performativity theory. The findings reveal that the lyrics of Talats Daqat represent gender bias both symbolically and structurally, positioning men as active subjects and women as passive objects. The application of Butler’s theory confirms that these representations are forms of gender performativity that reproduce and sustain gender inequality through popular cultural narratives. This research contributes by expanding the study of gender bias in Arabic through the integration of Butler’s critical theory and recommends the importance of critical approaches in Arabic language education to foster awareness of gender justice issues.